Peningkatan Aktivitas dan Hasil Belajar Siswa dalam Pembelajaran Kimia Menggunakan Model Pembelajaran Discovery Learning di SMA Negeri 1 Praya Barat - Sahnam, Sahnam (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2021)
This study aims to increase the activeness and learning outcomes of students' chemistry by applying the Discovery Learning learning model to electrolyte and non-electrolyte solutions at SMA Negeri 1 Praya Barat. This research is a classroom action research which is conducted in two cycles. The research subjects were all students of class X-MIPA-1 for the academic year 2019/2020, totaling 31 students. In this study, student learning activities were obtained through observation while learning outcomes were obtained through formative tests. The results of this study indicate; 1) Students' chemistry learning activities increase by applying the Discovery Learning learning model to the electrolyte and non-electrolyte solution material according to the two observations in Cycle I of writing and reading activities 50%, doing worksheets 20%, asking friends 10%, asking teachers 5%, and which are not relevant to teaching and learning activities 5% while according to the observations of Cycle II writing and reading activities are 21%, doing LKS 50%, asking friends 13%, asking teachers 16%, and those not relevant to teaching and learning activities 1%; 2) Students' chemistry learning outcomes increase by applying the Discovery Learning learning model to the electrolyte and non-electrolyte solution material in Formative I, showing 18 students completed individually, while the class was incomplete while in Cycle II, 28 students completed individually and the class completed with the average of cycle I and cycle II were 69 and 88 and the percentage of classical completeness was 58% in cycle I and 90% in cycle II.